2011
DOI: 10.2752/175303711x13045914865349
|View full text |Cite
|
Sign up to set email alerts
|

Exotic Animal Companions and the Personality of Their Owners

Abstract: The present study explored sex-specific differences in the Big Five factors of personality between different pet ownership groups, in order to understand individual differences in the choice of companion animals. A total of 250 pet owners completed a German version of the NEO-Five Factor Inventory (NEO-FFI). For the first analysis, participants were divided into four broad groups: those owning traditional pets (e.g., cats, dogs), those owning cold-blooded exotic pets, those owning warm-blooded exotic pets, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…None of our participants admitted to abandon pets, but the release of exotic pets poses a series threat to native wildlife world-wide if they are invasive, carry diseases or have maladaptive genes or behaviours as result of breeding, transportation and keeping practices (Hellebuyck et al, 2017;Karesh, Cook, Gilbert, & Newcomb, 2007;Lockwood et al, 2019;Magalhaes & Jacobi, 2013;Pasmans et al, 2017). Further study of the rate and the reasons behind the abandonment of the exotic pets in Russia is recommended.…”
Section: Further Researchmentioning
confidence: 94%
“…None of our participants admitted to abandon pets, but the release of exotic pets poses a series threat to native wildlife world-wide if they are invasive, carry diseases or have maladaptive genes or behaviours as result of breeding, transportation and keeping practices (Hellebuyck et al, 2017;Karesh, Cook, Gilbert, & Newcomb, 2007;Lockwood et al, 2019;Magalhaes & Jacobi, 2013;Pasmans et al, 2017). Further study of the rate and the reasons behind the abandonment of the exotic pets in Russia is recommended.…”
Section: Further Researchmentioning
confidence: 94%
“…In general, females with conventional pets, like cats and dogs, were less open to new experiences than were women who owned reptiles (Hergovich, Maurer, & Riemer, 2011). Female owners of birds and spiders were higher on agreeableness and openness than males of the same pet types; males owning cats and rodents were higher in agreeableness and openness than females with the same pets (Hergovich et al, 2011). Both studies showed significant differences among the personality of the owner and the type of pet they own.…”
mentioning
confidence: 78%
“…Means > 3.3 and standard deviation between 1.1 and 1.4 for all items loading on factor 2 indicate a somewhat smaller and more varying but nevertheless evident agreement to the social support the bird provides for the bird keeper (items 9-13). Quite similarly, means > 3.3 and standard deviation between 1.2 and 1.4 for all items loading on factor 4 indicate that in the owners' perceptions, most birds show a proximityseeking behavior toward the owner (items [19][20][21]. In contrast, the items loading on factor 1 show lower means (ranging from 2.6 to 3.8) and higher standard deviations (ranging from 1.3 to 1.5), reflecting the variance of agreement and disagreement to anthropomorphizing birds (items 1-8).…”
Section: Items Of the Owner-bird-relationship Scale (Obrs)mentioning
confidence: 90%